Antihyperglicemic effect of Musa paradisiaca extract in vivo - Hujjatusnaini, Noor; Nirmalasari, Ridha (Universitas Muhammadiyah Purwokerto, 2025)
Background: Musa paradisiaca hasÂ been widely studied for its antihyperglycemic effects, showing potential as an alternative natural remedy for diabetes. However, variability in genetic factors, environmental conditions, and geographical origins may influence its bioactive compound composition and efficacy. Thus, further validation through controlled studies is required to ensure consistent therapeutic effects.Purpose: : This study aimed to evaluate the antihyperglycemic effect of Musa paradisiaca stem extract in vivo, providing additional validation for its therapeutic potential and determining the optimal concentration for clinical relevance.Method: An experimental posttest-only control group design was used. Thirty-five male Balb/c strain mice were induced into hyperglycemia using alloxan. They were then randomly divided into treatment groups receiving different concentrations of Musa paradisiaca stem extract (5%, 15%, 25%, 35%, and 45%), a positive control group (metformin), and a negative control group. Blood glucose levels were measured and analyzed statistically using One-Way ANOVA.Result: Administration of the stem extract at 15% concentration showed the most significant antihyperglycemic effect, with an average blood glucose level reduction to 63.8 mg/dL, comparable to the positive control group (metformin). Conversely, the highest concentration tested (45%) exhibited minimal effectiveness, with an average glucose level of 151.8 mg/dL, indicating reduced antihyperglycemic activity.Conclusion: The optimal antihyperglycemic effect of Musa paradisiaca stem extract was achieved at a concentration of 15%, demonstrating therapeutic efficacy comparable to metformin. This extract shows promise as a natural alternative agent in diabetes treatment. Further studies, including clinical trials, are recommended to confirm these findings.